STRESS PADA LANSIA MENJADI FAKTOR PENYEBAB DAN AKIBAT TERJADINYA PENYAKIT - Hidaayah, Nur (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2013)
Stress conditions in the elderly means an imbalance condition of biological, psychological, and social are closely related to the response to the threats and dangers faced by the elderly. Pressure or interference that is not fun is usually created when the elderly see a mismatch between the state and the 3 systems available resources. Maintenance actions that need to be done there are 2 types, namely : prevention of exposure to a stressor (precipitation factor) and serious treatment of the imbalance condition/ illness (precipitation factor). Prevention includes: sports, hobbies, friendship, avoid eating foods high in free radicals and harmful substances, sex and setting arrangements adequate rest. Habits of the above if done at a young age to avoid exposure to stress in the elderly. Treatment of the imbalance condition / illness, include : drinking water, meditation, eating fresh fruit, and adequate rest.